Variabilidade temporal de propriedades físicas de um solo sob integração lavoura-pecuária - Zanchettin, Simone (2014)
The crop-livestock integration (ILP) consists of an association between agricultural crops and animal production in the same area, through alternating the cultivation of grain and pasture for livestock. The aim of this study was to evaluate the temporal variability of the physical properties of a soil under a Crop-Livestock Integration in system-till system. Density, porosity, microporosity, macroporosity and also the dry mass of plant residue: the following properties were evaluated. Four soil samples were taken: time after grazing, after planting season, after the harvest of corn and native forest. In the first season and in the forest 10 points were randomly collected in the area, in other epochs 10 points were collected in the row and between rows. The samples were taken at four depths: 0-5, 5-10, 10 15, 15-20 cm. Two samples of dry mass, a post-grazing and after the corn harvest was performed. For soil density and macroporosity no statistically significant difference between the treatments was observed, however for all depths the values found for macroporosity in treating post-grazing are below the critical value of 0.10 m³ m- 3. For total porosity and microporosity there was no statistical difference between sampling dates and the bushland in the 0-5, 5-10, 10-15 cm, while for the 15-20 cm depth there was no difference between treatments. The dry matter content observed increased after the corn harvest.